Embers of empire : continuity and rupture in the Habsburg Successor States after 1918 - Miller, Paul; Morelon, Claire (2019)
The end of World War I and the collapse of the Habsburg Monarchy marked a period of radical change for East-Central European political structures and national identities. Yet after the dust had cleared, this transformed landscape still bore many traces of its imperial past. Breaking with traditional histories that take 1918 as a strict line of demarcation, this collection focuses on the complexities that attended the transition from the Habsburg empire to its successor states. In so doing, it produces new and more nuanced insights into the persistence and efficacity of imperial institutions, as well as the sources of instability in the newly formed nations